The Rare Books of the Galway Poor Clares. (2nd December 2021) - Goodrich, Jaime
Abstract: The Poor Clares of Galway are the oldest surviving convent in Ireland, maintaining a small but important collection of rare books from the seventeenth and eighteenth centuries. This essay offers a bibliographical analysis of these rare books in order to sketch the role of reading within the convent from the seventeenth through the twentieth centuries. By analysing material evidence of reading and circulation practices—signatures, readers' marks, marginalia, and bookmarks—broader patterns of book usage among the Galway Poor Clares are reconstructed for the first four centuries of existence. The essay concludes with a short bibliographical catalogue of the convent's special collections.